1985
DOI: 10.1115/1.3225774
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Equation of Cyclic Softening

Abstract: A constitutive equation of cyclic strain softening for materials with low internal stress levels was derived from the rate equation. The study showed that cyclic strain softening is associated with stress relaxation and that the two phenomena are parallel over a high stress and low temperature range where thermally activated plastic flow in the two processes can be approximated with activation over a single energy barrier. The constitutive parameters were identical in both processes, leading to the recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The constitutive equation of cyclic strain softening for materials with low (or negligible) internal stress levels was derived in our previous paper [16]. The study showed that cyclic strain softening is a rate phenomenon, strongly dependent on the temperature and loading rate, and that it can be tested in stress relaxation.…”
Section: Constitutive Equation Of Cyclic Strain Softeningmentioning
confidence: 99%
See 4 more Smart Citations
“…The constitutive equation of cyclic strain softening for materials with low (or negligible) internal stress levels was derived in our previous paper [16]. The study showed that cyclic strain softening is a rate phenomenon, strongly dependent on the temperature and loading rate, and that it can be tested in stress relaxation.…”
Section: Constitutive Equation Of Cyclic Strain Softeningmentioning
confidence: 99%
“…In our previous papers [16,17] it was considered that plastic flow during cyclic strain softening is a thermally activated process and the constitutive equation describing the shear stress in function of time during cyclic strain softening was derived. It was shown that cyclic strain softening is associated with stress relaxation and that the two phenomena are parallel over a high stress and low temperature range where thermally activated plastic flow in the two processes can be approximated with activation over a single energy barrier.…”
Section: Thermally Activated Cyclic Softeningmentioning
confidence: 99%
See 3 more Smart Citations